MODEL PROBLEM BASED INTRODUCTION DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 42 PIDIE - Nia Wardhani; Nuraliza (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2020)
This study aims to determine the application of the Problem Based Introduction (PBI) model in improving the learning outcomes of 4th grade students of MIN 42 Pidie. These type of research was Classroom Action Research with the research subjects being 19 fourth-grade students of MIN 42 Pidie. Data analysis techniques were using observation, tests, and documentation. In cycle I, the average value obtained by students was 41.57 with classical completeness of 15.78%. In cycle II, the average value obtained by students was 52.10 with classical completeness of 42.10%. And in cycle III, the average value was 83.68 with classical completeness of 89.47%. So it can be concluded that the application of the Problem Based Introduction (PBI) model can improve the learning outcomes of 4th grade students of MIN 42 Pidie.